Egy nemzeti hős születése A Petőfi-emlékezet kialakulása - Owaimer Oliver (2025)
In our dissertation we tried to explore the history of the beginnings of Petőfi’s memory. We approached the subject of our study within a comprehensive systems-theoretical framework, which led us to identify the most important social subsystems of the mid-19th century in terms of memory: the fields of science, art and the mass press. These subsystems is as closed, self-contained units of society, usually cooperating with each other in the common interest, through structural links of movement. The first chapter started with a theoretical overview of some key concepts: collective memory and its co-concepts. In the second chapter, we traced the increasingly distinctive and differentiated discursive assertion of historiography in Petőfi’s memory. We proceeded in chronological order, from the earliest Petőfi legends to the first complete biography, published in 1864. In the third part we turned to the artistic manifestations of collective memory. This time, instead of the linear-chronological approach we had taken before, we adopted a vertical-synchronous cross-section to analyse Petőfi’s representations belonging to different cultural registers. Finally, we have studied the workings of the press as a space for the formation of Petőfi’s memory. After the diachronic and synchronic overviews, we proceeded in a concentric process: from a holistic examination of the press sources, through the memorial poems, mostly published in the press, to János Arany’s first cycle of poems, Emlények (1851-55), published in his first book of poems. One of the starting points for our argument is that in the 19th century a new, modern, scientific narrative (grand récit) took over the funcion of the community building from the national grand epos, which had previously been expected in vain. We believe that if one could name the hero („héros”) of the modern Hungarian „epos”, created mainly by science and literature together, it would undoubtedly be the Slovak-born Hungarian poet Sándor Petőfi.